Penggunaan Aplikasi Atlas dalam Audit Laporan Keuangan - Kazza Savanah Zubaidi; Munari Munari (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The development of the globalization era, especially through advances in digital technology, has had a significant impact on the practice of auditing financial statements. The application of the ATLAS (Audit Tools and Linked Archive System) application published by the Financial Professional Development Center of the Ministry of Finance is proof of how information technology is changing the audit paradigm from traditional to modern. ATLAS facilitates the audit process in accordance with the audit standards contained in the International Standards on Auditing (ISA) which includes the risk assessment stage, risk response stage, and reporting stage. The research method used is descriptive qualitative, based on historical data which includes literature and studies from previous research as well as the results of interviews with auditor staff from one of the KAPs in Surabaya. All information collected is then analyzed and conclusions are drawn based on the research results. The research findings in this article highlight the advantages of the ATLAS application in collecting and analyzing data more accurately and quickly, as well as strong security features to protect data integrity during the audit process. Although there were initial challenges related to the complexity of using this application, the adaptations made by auditors had a long-term positive impact on the audit process.